Study on the performance of the investigation and repair material of asphalt pavement crack diseases. Issue 1 (April 2019) - Li, Junwei; Yang, Yang
Abstract: Rutting and cracks are the main diseases of asphalt pavement at home and abroad. Based on the investigation of a highway, the author studies the degree of cracks on the highway and the main causes. According to the characteristics of pavement diseases, the corresponding treatment measures are put forward. Through laboratory tests, it is determined that the fibre repairing materials have a good effect on improving the low temperature anti cracking performance of asphalt mixture, and can be preferentially considered as pavement repairing materials.